Pengaruh Intensitas Modal, Pertumbuhan Penjualan, dan Kepemilikan Institusional terhadap Agresivitas Pajak dengan Financial Distress Sebagai Variabel Moderasi - Yussi Dwi Luthfiah; Linawati Linawati (Universitas 17 Agustus 1945 Jakarta, 2026)
This study aims to examine the effect of capital intensity, sales growth, and institutional ownership on tax aggressiveness with financial distress as a moderating variable. This research employs a quantitative approach using purposive sampling on property and real estate companies listed on the Indonesia Stock Exchange during 2020–2024. The results indicate that capital intensity and institutional ownership do not affect tax aggressiveness, while sales growth affects tax aggressiveness. In addition, financial distress is able to moderate the effect of capital intensity on tax aggressiveness, sales growth on tax aggressiveness, and institutional ownership on tax aggressiveness. Therefore, companies need to consider financial conditions and tax policies to reduce the potential for tax aggressiveness.